Comparative cost assessment of sustainable energy carriers produced from natural gas accounting for boil-off gas and social cost of carbon - Mohammed Al-Breiki (14152476) (2020)
As a result of particular locations of large-scale energy producers and increases in energy demand, transporting energy has become one of the key challenges of energy supply. For a long-distance ocean transportation, transfer of energy carriers via ocean tankers is considered as a decent solution compared to pipelines. Due to cryogenic temperatures of energy carriers, heat leaks into storage tanks of these carriers causes a problem called boil-off gas (BOG). BOG losses reduce the quantity of energy carriers, which affects their economic value. Therefore, this study proposes to examine the effects of BOG economically in production and transportation phases of potential energy carriers produced from natural gas, namely; liquefied natural gas (LNG), dimethyl-ether (DME), methanol, liquid ammonia (NH3), and liquid hydrogen (H2). Mathematical approach is used to calculate production and transportation costs of these energy carriers and to account for BOG as a unit cost within the total cost. The results of this study show that transportation costs of LNG, liquid ammonia, methanol, DME, and liquid hydrogen from natural gas accounting for BOG are 0.74 $/GJ, 1.09 $/GJ, 0.68 $/GJ, 0.53 $/GJ, and 3.24 $/GJ, respectively. DME and methanol can be more economic compared to LNG to transport the energy of natural gas for the same ship capacity. Including social cost of carbon (SCC) within the total cost of transporting the energy of natural gas, the transportation cost of liquid ammonia is 1.11 $/GJ, whereas LNG transportation cost rises significantly to 1.68 $/GJ at SCC of 137 $/t CO2 eq. Consequently, liquid ammonia becomes economically favored compared to LNG. Transportation cost of methanol (0.70 $/GJ) and DME (0.55 $/GJ) are also lower than LNG, however, liquid hydrogen transportation cost (3.24 $/GJ) is still the highest even though the increment of the cost is about 0.1% as SCC included within the transportation cost. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2020.07.013